2018
DOI: 10.1002/nml.21311
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a model of servant leadership, empowerment, and commitment in nonprofit organizations

Abstract: This study examined a model of servant leadership's relationship to organizational commitment through structural and psychological empowerment, focusing on leader–follower dyads in a nonprofit organization. Survey data was collected from 128 employees of a nonprofit organization in a northeastern U.S. city. After model re‐specification, a well‐fitting model emerged, indicating that structural empowerment mediates the relationship between servant leadership and organizational commitment. Moreover, the model sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 64 publications
(164 reference statements)
6
59
0
2
Order By: Relevance
“…Empowering leadership delegates authority and autonomy to employees, allowing them to work with confidence, value their contributions, and make their work more meaningful [19]. Through participative decision-making of empowering leadership [45], employees gain a sense of control over their performance and feel psychological empowerment [19], which can increase organizational commitment [33,46]. Psychological empowerment is an important factor in organizational change, as it allows employees to have control over their work and influence the process of organizational change [33,47].…”
Section: Empowering Leadership and Commitment To Organizational Changementioning
confidence: 99%
“…Empowering leadership delegates authority and autonomy to employees, allowing them to work with confidence, value their contributions, and make their work more meaningful [19]. Through participative decision-making of empowering leadership [45], employees gain a sense of control over their performance and feel psychological empowerment [19], which can increase organizational commitment [33,46]. Psychological empowerment is an important factor in organizational change, as it allows employees to have control over their work and influence the process of organizational change [33,47].…”
Section: Empowering Leadership and Commitment To Organizational Changementioning
confidence: 99%
“…In other words, committed workers are more likely to remain in the organization than those who are uncommitted (Meyer & Allen, 1997). Organizational commitment generally refers to the individual's identification with and involvement in a particular workplace (Allen, Winston, Tatone, & Crowson, 2018), whereas affective commitment refers to an individual's emotional attachment to the organization (Meyer & Allen, 1991). Affective commitment, arguably the most pertinent form of employee commitment for nonprofit organizations (Erdurmazli, 2019), is an attitudinal process whereby employees think about their relationship to the organization with respect to their values and goals (Meyer & Allen, 1991).…”
Section: Affective Commitment and Performancementioning
confidence: 99%
“…Several studies have examined the impact of psychological empowerment (i.e., intrinsic motivation) on work satisfaction [23,24], organizational commitment [25,26] and performance [27,28]. Moreover, recent studies have confirmed that the higher the level of employees' psychological empowerment, the more motivated employees are to perform well and demonstrate more at work [29][30][31].…”
Section: Introductionmentioning
confidence: 99%